Interv'iu s deputatom Verkhovnogo Soveta RF Travkinym i s ministrom inostrannykh del RF A.Kozyrevym . Interv'iu s deputatom Verkhovnogo Soveta RF Travkinym i s ministrom inostrannykh del RF A.Kozyrevym . Interviews with Travkin, Deputy of the Supreme Soviet of the Russian Federation and A.Kozyrev, Minister of Foreign Affairs of the Russian Federation . Интервью с депутатом Верховного Совета РФ Травкиным и с министром иностранных дел РФ А.Козыревым - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Talks on economic reforms. Обсуждение экономических реформ.